Empiric reliability of diagnostic and prognostic estimations of physical standards of children, going in for sports. - Zaporozhanov V.A; Boraczynski Tomasz (Kharkov National Pedagogical University, 2012)
In the conditions of sporting-pedagogical practices objective estimation of potential possibilities gettings busy already on the initial stages of long-term preparation examined as one of issues of the day. The proper quantitative information allows to individualize preparation of gettings in obedience to requirements to the guided processes busy. Research purpose - logically and metrical to rotin expedience of metrical method of calculations of reliability of results of the control measurings, in-use for diagnostics of psychophysical fitness and prognosis of growth of trade gettings busy in the select type of sport. Material and methods. Analysed the results of the control measurings on four indexes of psychophysical preparedness and estimation of experts of fitness 24th gettings busy composition of children of gymnastic school. The results of initial and final inspection of gymnasts on the same control tests processed the method of mathematical statistics. Expected the metrical estimations of reliability of measurings is stability, co-ordination and informing of control information for current diagnostics and prognosis of sporting possibilities inspected. Results. Expedience of the use in these aims of metrical operations of calculation of complex estimation of the psychophysical state of gettings busy is metrology grounded. Conclusions. Research results confirm expedience of calculation of complex estimation of psychophysical features gettings busy for diagnostics of fitness in the select type of sport and trade prognosis on the subsequent stages of preparation.